Multimodal Elimination for Intoxication with a Lethal Dose of Organic Mercury - L. C. Napp; C. Moelgen; F. Wegner; P. Heitland; H. D. Koester; M. Klintschar; M. Hiss; A. Schaper; B. Schieffer; J. Bauersachs; A. Schäfer; J. Tongers (Case Reports in Critical Care)
We here report on a case of massive organic mercury intoxication in a 40-year-old man that resulted in progressive multiorgan failure. We treated the patient intravenously and enterally with the chelating agent (RS)-2,3-bis(sulfanyl) propane-1-sulfonic acid (DMPS) in addition to hemodialysis. The patient was treated for 6 weeks and could successfully be weaned from mechanical ventilation and hemodialysis. He awoke and was sent to rehabilitation, but unfortunately died 7 months later from refractory status epilepticus. Autopsy revealed severe brain atrophy consistent with organ damage from massive mercury intoxication. The present case illustrates that bimodal DMPS application is sufficient for detoxification from lethal mercury levels, with an associated chance for weaning of organ support and survival to discharge. The case further reminds us of intoxication as a cause of multiorgan dysfunction. We propose to immediately initiate combined parenteral and enteral detoxification in cases of methyl mercury intoxication, especially in cases of high doses.